Quasi Experimental Study to Evaluate the Impact of Psychoeducational Intervention on Level of Anxiety among Hospitalized Children (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background of the study: There are various way to provide Psycho-education(PI) to the patientadmitted in the hospital. It is broadly steered by four main goals: transfer of information, medicationand treatment support, training and support in self-help and self-care, and the provision of a safe placeto vent emotional frustrations.An excessive or persistent state of anxiety leads devastating effect on children’s physical as well as mentalhealth. Psych education is scientifically proved therapeutic intervention which helps to the client along withfamily members to cope with illness and give the information as well as support to understand in better way.Psych education is helps to children and their family to minimize the emotional trauma during the hospitalstay.Objective:1) To determine the impact of psycho educational intervention on anxiety level among children withhospitalization.2) To find out the association between socio demographic variable with the pre intervention anxiety levelamong hospitalized children.Methodology: The study was executed by using quantitative research approach with quasi experimentaldesign. The study was conducted at selected three hospitals of Anand district, two hospital of Vadodaradistrict and one Hospital of Ahmedabad District, Gujarat. 33 Hospitalized 6 – 12 year old children wereselected for each experimental group and control group using convenient sampling technique. For bothgroups, Pre-intervention anxiety level assessment was done using Performa of demographic variables,Modified Hamilton Rating Scale. Psycho educational intervention included play book and guided imageryadministered to the 6-12 year old hospitalized children of experimental group for duration of 30 minutesfor 3 consecutive days. On third day anxiety level have been level done on third day after 5 hours from lastintervention.